From Gamification to Student Achievement: A Longitudinal Conceptual Structure Analysis of a Research Field - Papadakis, Stamatios; Karakose, Turgut; Yirci, Ramazan; Tulubas, Tijen; Demir, Irem (MDPI, 2026)
Gamification has become an innovative method used to enrich instructional designs, moving far beyond its initial motivational purposes. Given its promising impact on the contemporary educational context, gamification has attracted numerous studies seeking ways to enhance the quality of instruction and learning outcomes across diverse fields. Despite the growing volume of gamification research, longitudinal analyses tracing how the conceptual priorities of the field have shifted across historically distinct periods remain scarce. This study addresses that gap by mapping the thematic evolution of gamification research through science mapping analysis of articles published in peer-reviewed journals across three time periods: 2006-2019, 2020-2022, and 2023-2025. The findings indicate that early research focused primarily on gamification's impact on student motivation and engagement, while subsequent research focused on course evaluation and digital learning environments. Recent research has focused more on blended and domain-specific methods, testing the adaptability of different applications to specific fields. These findings suggest that gamification research has evolved from more superficial practices, such as encouraging course participation or boosting motivation, to its integration into personalized learning environments, and in recent years, towards ethical data use and the development of context-specific applications.
Keywords: gamification; adaptive learning; blended learning; student achievement; science mapping; SciMAT; INTRINSIC MOTIVATION; CLASSROOM; Computer Science